(3eTGQY GdCThGbs - (3CHhYHO Gddg HgGA GdOjf eMeO Hf EHQGgje Hf eMeO Hf GdfMGS GdMdHj,J (B698 (3g` s
(3ChdgG (B:s
(3CeG HYO QCjJ Gdgee bGUQI Yf Gddg JYGdi hYf WQjb GdhUd Edjg SHMGfg s
(3BNQgG (B:s
(3hGdMeO ddg Gddge dLejY GdeDefjf hGdeDefGJ hGdeSdejf hGdeSdeGJ GdCMjGA efge hGdCehGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1686s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs